Financial and extra-financial determinants of CEOs’ sustainable discourse: A longitudinal analysis on the US market - Lachuer, Julien; Jost, Sébastien (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
The aim of this paper is to identify, through the discourse, the managerial sustainable behaviors that lead to both financial and extra-financial performance. Under the prism of alignment and instrumental theories on corporate social responsibility (CSR), we investigate the moderating role of CEOs by examining the interrelation between CEOs’ introductory discourses in sustainability reports and financial and extra-financial performance. Through the use of a logit model and textual analysis, we conduct a longitudinal analysis on firms listed on the S&P500 between 2014 and 2019 in three sectors. We find that CEOs’ discourse is interrelated with financial and extra financial performance. Their discourse is a key factor in understanding whether CEOs’ CSR strategies meet the main sectorial strategic issues.